Developing an Experiential Definition of Recovery: Participatory Research With Recovering Substance Abusers From Multiple Pathways. (28th July 2016) - Borkman, Thomasina Jo; Stunz, Aina; Kaskutas, Lee Ann
ABSTRACT: Background : The What is Recovery? (WIR) study identified specific elements of a recovery definition that people in substance abuse recovery from multiple pathways would endorse. Objectives : To explain how participatory research contributed to the development of a comprehensive pool of items defining recovery; and to identify the commonality between the specific items endorsed by participants as defining recovery and the abstract components of recovery found in four important broad recovery definitions. Methods : A four-step, mixed-methods, iterative process was used to develop and pretest items (August 2010 to February 2012). Online survey recruitment ( n = 238) was done via email lists of individuals in recovery and electronic advertisements; 54 were selected for in-depth telephone interviews. Analyses using experientially-based and survey research criteria resulted in a revised item pool of 47 refined and specific items. The WIR items were matched with the components of four important definitions. Results : Recovering participants (1) proposed and validated new items; (2) developed an alternative response category to the Likert; (3) suggested criteria for eliminating items irrelevant to recovery. The matching of WIR items with the components of important abstract definitions revealed extensive commonality. Conclusions/Importance : The WIR items define recovery as ways of being, as a growth and learning process involving internal values and self-awareness with moral dimensions. This is the first wide-scale research identifying specific items defining recovery, which can be used to guide service provision in Recovery-Oriented Systems of Care.